(untitled) (Fiep Bulletin - online, 2013)
At the present is in Slovakia the new education law put into the practice. This new law brings several more changes into the life of schools. In the structure of schools is coming the new ISCED system into effort, the new two-level curriculum is being introduced – the State Education Program and school education programs, educational areas are introduced, also the cross-section topics, maximum number of students per class is regulated, the content of education in particular subjects is changed. It changes also the character of school physical and sport education (TŠV) (Antala – Labudová, 2008). The state educational program determines also the exact number of lessons in particular subjects in particular grades of education. To this lessons may lock on by means of free lessons under the terms of school educational programs. About the utilization of free lessons of the school educational programs each school will decide on its own. At the point of decision making the decisive word will belong mostly to the headmasters and representatives of schools. That´s why we were interested in the current representation of the teachers of physical and sport education in managerial positions.